Brand or Experience Driven? Dual Pathways to Patient Loyalty in Healthcare - Ni Wayan Suardhani; I Gede Riana; Ni Luh Komang Candra Dewi (Jambura Science of Management, 2026)
Purpose: This study investigates whether brand awareness shapes patient loyalty through the mediating roles of patient satisfaction and patient engagement, and whether this mechanism differs between BPJS (national health insurance) and non-BPJS patients of a private hospital network in Bali, Indonesia. The study draws on Expectation-Confirmation Theory (ECT) to explain how cognitive and relational pathways translate brand recognition into long-term loyalty.Design/Methodology/Approarch: A quantitative comparative survey was conducted among 150 patients of RS. Kasih Ibu Bali (75 BPJS and 75 non-BPJS), selected through purposive sampling across four hospital branches. Data were collected with a validated 24-item, five-point Likert questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4, followed by Measurement Invariance of Composite Models (MICOM) and Multi-Group Analysis (MGA) using Henseler's nonparametric test and permutation procedures.Findings: For BPJS patients, brand awareness directly and strongly predicted loyalty, while satisfaction and engagement played no significant role. For non-BPJS patients, the opposite pattern emerged: brand awareness had no direct effect on loyalty, whereas satisfaction and engagement were the dominant drivers. Satisfaction mediated the brand awareness-loyalty link significantly only among non-BPJS patients, while serial mediation through satisfaction and engagement together was not supported in either group. These results indicate that patient loyalty in a two-tier healthcare financing context follows two structurally distinct psychological routes: a brand-driven route for BPJS patients and an experience-driven for non-BPJS patients. Practical implications for differentiated hospital marketing and service-quality strategies are discussed.